Development of Cerebral Metastasis after Medical and Surgical Treatment of Anal Squamous Cell Carcinoma - Andrew Austin Gassman; Emil Fernando; Casey Jacob Holmes; Umesh Kapur; Joshua M. Eberhardt (Case Reports in Oncological Medicine)
Squamous cell carcinoma of the anus is a relatively uncommon GI malignancy. When it does occur, it metastasizes in only a small minority of patients. Spread of anal squamous cell carcinoma to the brain is exceedingly rare, and has been previously reported only three times in the medical literature. We report the case of a 67 year old male who was diagnosed on presentation with a poorly differentiated anal squamous cell carcinoma that already had a solitary metastasis to the liver. While the tumors were initially responsive to chemoradiotherapy, the patient’s primary and liver lesions recurred. The patient then underwent synchronous abdominoperineal resection for the primary lesion and a liver lobectomy for the metastasis. Soon thereafter, the patient developed focal neurologic symptoms and was found to have an intracranial lesion that on biopsy demonstrated metastatic squamous cell carcinoma. This case highlights the fact that patients with a previous history of anal squamous cell carcinoma can occasionally develop cerebral metastasis. Furthermore, cerebral metastases from anal squamous cell carcinoma portend a dismal prognosis even in the face of aggressive medical and surgical therapy.